The ecology of and fishery for Coryphaena spp. in the waters around Australia and New Zealand - Kingsford, Michael J.; Defries, Anthony (Scientia Marina, 1999)
Two species of dolphinfish, Coryphaena hippurus and Coryphaena equiselis, are found in Australian waters and off the north-eastern coast of New Zealand. Both species (also called Mahi-mahi, or dorado) are generally found in tropical waters, but only C. hippurus is captured in southern waters (to 34°S). Dolphinfish are caught by recreational and commercial fishers, using either trolled or baited lines. Most catch records do not allow the identification of fish to the species level. Dolphinfish are also an incidental catch of foreign and domestic pelagic fisheries (e.g. long-lining for tunas and billfishes) and 10-70 tonnes are taken per year in the Australia-New Zealand region. Although Coryphaena are known to associate with objects (e.g. traps for carangids and navigation buoys) and are a focus for recreational fishers, Fish Attraction Devices (FADs) are not used by commercial fishers off the coast of Australia and New Zealand. FADs are, however, used by fishers in the Pacific Islands. Recreational catches of Coryphaena may exceed the commercial catch in some areas. Good data for New South Wales, Australia, gave estimates of 11.7 and 12.7 tonnes of Coryphaena caught in 1994 and 1995 respectively, which represented 1.1-1.8x the recorded commercial catch. Approximately ~12,600 fish have been tagged since 1973 around Australia and data on returns are only available for 108 fish (0.86% recovery). Tagged Coryphaena were found to move distances of up to 440 kilometres and at estimated speeds of up to 20 kilometres per day. The time between tag and recapture varied from 0-360 days and fish moved 0-440 kilometres. The majority of fish were caught around the same drifting object near where they were tagged. The collection of Coryphaena larvae in Queensland and New South Wales, along the east coast of Australia, indicates spawning in these waters. Most larvae have been collected in the austral summer and autumn and typically in surface waters well offshore. Dolphinfish have been successfully raised from eggs to fish of marketable size in Western Australia and the species appears to be an excellent candidate for mass production, which is now possible in Australia.